ІНТЕЛЕКТУАЛЬНІ ТЕХНОЛОГІЇ МОНІТОРИНГУ ТЕХНІЧНОГО СТАНУ СУЧАСНИХ ВИСОКОВОЛЬТНИХ КАБЕЛЬНИХ ЛІНІЙ ЕЛЕКТРОПЕРЕДАЧІ - Кириленко, О.В.; Щерба, А.А.; Кучерява, І.М. (Інститут електродинаміки НАН України, Київ, 2021)
The review concerning application of fiber-optic technologies in power industry, in particular, for monitoring of modern power cables with cross-linked polyethylene insulation and integrated fiber-optic module is carried out. The new intelligent tools for control of electrical, thermal and mechanical characteristics and partial discharges in power cable lines are presented. The current operational experience for the system of Smart Cable Guard in an emergency is described. The prospects to develop and use the intellectual technologies for monitoring of technical state of up-to-date high-voltage cable power lines and their operate reliability are grounded by analysis of new diagnostic methods controlling the level of partial discharges, temperature distribution and mechanical damage in polyethylene insulation and other elements of the high- and extra-high-voltage cables with integrated fiber-optic modules. References 51, figures 8.